2022
DOI: 10.17309/tmfv.2022.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Sport Model to Improve Fundamental Movement Skills and Social Attitudes of Students During COVID-19

Abstract: The study purpose. COVID-19 caused many negative impacts, including a significant decrease in the fundamental movement skills and social attitudes among students, which becomes the main problem in this study. Therefore, this study aims to investigate the effect of traditional sport on improving students’ fundamental movement skills and social attitudes. Materials and methods. This study adopted an experimental method with a pretest-posttest design. The subjects were elementary school students in Yogyakar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
1
12
0
2
Order By: Relevance
“…The study found that using games and physical activities in learning can enhance children's gross motor skills (Aliriad et al, 2024;Nur et al, 2020;Sutapa & Suharjana, 2019). Similarly, research results have shown that integrating gaming elements into learning can improve coordination and motor control in elementary school students (Mujriah et al, 2022;Saputra et al, 2021;Suryadi et al, 2023). Therefore, these findings affirm that gamification in physical education not only enhances students' interest and participation but is also effective in improving their motor skills.…”
Section: Discussionmentioning
confidence: 57%
“…The study found that using games and physical activities in learning can enhance children's gross motor skills (Aliriad et al, 2024;Nur et al, 2020;Sutapa & Suharjana, 2019). Similarly, research results have shown that integrating gaming elements into learning can improve coordination and motor control in elementary school students (Mujriah et al, 2022;Saputra et al, 2021;Suryadi et al, 2023). Therefore, these findings affirm that gamification in physical education not only enhances students' interest and participation but is also effective in improving their motor skills.…”
Section: Discussionmentioning
confidence: 57%
“…The study of the cardiovascular and respiratory indicators in patients of the control and main groups showed positive time course was observed in terms of pulse and blood pressure (Mujriah et al, 2022). When comparing the obtained repeated indicators of the cardiovascular and respiratory systems between the control and the main group, no significant differences were found, which indicates a positive effect of complex physical rehabilitation on women in both groups.…”
Section: Discussionmentioning
confidence: 80%
“…This makes traditional games the right alternative in developing physical literacy. Several studies on traditional Lombok games that have been explored through research (Irmansyah et al, 2021;Kurniawan et al, 2020;Mujriah et al, 2022) have not found their relevance and are focused on increasing children's physical literacy. This is the basis and logical justification, as well as the uniqueness of this study, because it accommodates various traditional Lombok games, such as Ketik Jaran, Begelompongan, Kideng, Begatrik, Panji (to mention a few).…”
Section: Introductionmentioning
confidence: 99%